Economic Feasibility Analysis of Local Road Maintenance in West Bandung Regency: A Case Study of Cangkorah Street STA 0+000 – 1+300 - Ery Radya Juarti; Atmy Verani Rouly Sihombing; Yola Widi Pratiwi; Sekar Fadillah (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
This study aims to determine the economic feasibility of the local road maintenance scenario in West Bandung Regency with a case study of Cangkorah Street. As a strategic road to pass through the route to the city of Bandung and have a heavy traffic with a lot of heavy vehicles pass the road, roads must be maintained in order to create a safe and comfortable road for passengers. There are several ways to maintain the road, one of them is direct survey using IKP guidelines. The result from IKP value by using IKP guidelines will produce in an International Roughness Index (IRI) values the economic feasibility analysis is carried out based on a road maintenance scenario, while the maintenance scenario being tested is a do- something scenario, by doing road maintenance in the form of overlay once every 5 years in 10 year time compared by a do-nothing scenario that is not doing any maintenance for the next 10 years. The research instruments used were prediction of the performance of the Cangkorah Street Pavement for the next 10 years, determine road maintenance scenarios, maintenance budget plans, calculate Vehicle Operational Costs (VOC) for each scenario, and time value. The conclusion of the study is comparing to the scenarios, do-nothing and do-something, the feasibility of do- something scenario from an economic point of view shows that the scenario is feasible with NPV is Rp. 36,674,480,6270 and a BCR of 11.391.